Penerapan Arsitektur Hijau pada Perancangan Coconut Center di Gorontalo - Rahmawati Juniar Lahay; Heryati Heryati; Niniek Pratiwi (Universitas Medan Area, 2026)
Coconut is a viral economic commodity for Indonesians due to its abundant yield. In Gorontalo, there also vast coconut plantations; however, the production of the commodity has not been optimized. Therefore, the design of the Coconut Center aims to maximize the potential of the coconut by accommodating three classified activities: primary, secondary, and supporting. The primary activity involves educational toirism. The supporting activities include management and other facilities that assiist the primary and secondary functions. The study employed three main data collection techniques; interview, direct observation, and literatura review. The design process involved collecting relevant data, identifying problems, defining design goals, and compiling theoretical frameworks to support architectural planning. The resulting analysis is then transformed into a Green architecture design concept. This concept serves as a guideline for designing the Coconut Center in Gorontalo.